Effective meetings : teacher's book - Comfort, Jeremy; York Associates (Oxford [England] : Oxford University Press, 1996)
This book is divided into eight units which deal with the major stages of a meeting, from preparation through to decision-making and follow-up action to develop essential communication and language skills.
Keywords: Meetings; Meetings -- Planning; Meetings -- Audio-visual aids; English language -- Usage -- Study and teaching